A novel wearable wideband antenna for application in wireless medical communication systems with jeans substrate. Issue 8 (3rd August 2021) - Khajeh-Khalili, Farzad; Khosravi, Yasaman
Abstract: In this paper, a novel wearable wideband antenna for application in wireless medical communication systems (0.9–6 GHz) is designed. For bandwidth enhancement, five parallel metal plates (PMPs) are placed on the top of the antenna's patch without any disturbing effects on the performances. With the help of the proposed method, the bandwidth has been increased by about 3 GHz in comparison with the conventional one. The antenna dimensions are 60 × 48 × 0.8 mm 3 or 0.72 × 0.57 × 0.009 λg 3 where λg is the guided wavelength at 2.4 GHz. Simple design, wearable, wide bandwidth, and compact size are the most important benefits of the proposed antenna. Finally, to prove the simulations and designs, the proposed antenna was fabricated. The measurement outcomes are also consistent with the simulation results.